Prolonged Allograft Survival In Newcastle Disease Virus-Treated Mice - Woodruff, Jack F. (1974)
There was persistent lymphocytopenia and prolonged survival of C57Bl skin allografts when recipient BALB/c mice were injected daily with Newcastle disease virus.